1999
DOI: 10.1111/j.1151-2916.1999.tb01996.x
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of Lead Zirconate Titanate for Fused Deposition of Ceramics

Abstract: A study of the adsorption of several surfactants onto lead zirconate titanate (PZT) powder was performed. The adsorption of oleyl alcohol, stearyl alcohol, oleic acid, and stearic acid onto PZT-5H powder (surface area = 2.58 m 2 /g) was measured by thermogravimetric analysis. Toluene was used as a solvent, and the solution concentrations were set at 50.0 g/L. It was found that the stearic acid adsorption onto the PZT-5H powder was highest, to the extent of 8.1 mg/m 2 . Trace amounts of stearyl alcohol adsorbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…There have been studies conducted that establish the efficacy of each surfactant in reducing the viscosity of the filled systems to values that permit their use in FDC. In the case of stearic acid and ECG9 system, the stearic acid molecule is thought to function primarily as a dispersant for the case of PZT/ECG9 as discussed by McNulty [42].…”
Section: Filament Fabricationmentioning
confidence: 98%
See 3 more Smart Citations
“…There have been studies conducted that establish the efficacy of each surfactant in reducing the viscosity of the filled systems to values that permit their use in FDC. In the case of stearic acid and ECG9 system, the stearic acid molecule is thought to function primarily as a dispersant for the case of PZT/ECG9 as discussed by McNulty [42].…”
Section: Filament Fabricationmentioning
confidence: 98%
“…The exact values of shrinkage vary from one material to another. The shrinkage values for PZT are 16% and 20% respectively [39,42]. As can be seen from the shrinkage values for PZT, there is significant anisotropy in the shrinkage i.e.the shrinkage in the build direction tends to be higher than in the build plane directions [39,42].…”
Section: Post-processingmentioning
confidence: 98%
See 2 more Smart Citations
“…McNulty et al (59) studied the essential requirements of feedstock filaments for the FDC process because the key to the success of the FDC is the filaments with required mechanical and rheological properties. They investigated the effect of several surfactants on the lead zirconate titanate (PZT) powder and found that the stearic acid was a suitable surfactant for FDC to aid coating and dispersion of the powder in the polymer matrix used to make filaments.…”
Section: Ceramics In Fdmmentioning
confidence: 99%